Does Brainstorming in Supervision Audit Fieldwork Can Improve Professional Auditor Judgement ? - Apandi, Nelly Nur; Rossieta, Hilda; Fitriany, Fitriany; Wondabio, Ludovicus Sensi (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This research was aimed to see supervision audit fieldwork using brainstorming approach can improve professional auditor judgment in assessing the risk of material misstatement. Method used was experiment with participants were 293 accounting students in 21 higher education institutions in Indonesia. Result of research indicated that Participant with verbal brainstorming treatment and Participant with written brainstorming treatment have better judgment to assess the risk of material misstatement than and with no brainstorming treatment. Professional Judgment increases because the auditor is given a better understanding of the probability and impact of risk. This study has implication for audit practices, audit supervision is needed by junior auditors to improve audit quality.Brainstorming can help the auditor assess the risk of material misstatement properly.